Lighting the Way in Manipur : Post Unbundling Reforms in Distribution - Mittal, Rohit; Saraswat, Kavita; Gupta, Amol; Gaba, Kwawu Mensan (World Bank, Washington, DC, 2016)
Simple economic principles tell us that investment begets investment and wealth creates wealth. Investment of money alone, however, is seldom enough to trigger this virtuous cycle, time, effort and substantial planning are also critical elements. This working paper captures the story of transformation of Manipur’s electricity distribution sector which has laid the foundation for a slow but sure transformation of a state that has seen more than its share of troubled times. This paper is about a World Bank-supported Government of Manipur’s initiative to improve and institutionalize efficient commercial, Operation and Maintenance (O&M), project-related systems and processes, institutional strengthening and creation of a robust review and monitoring mechanism for the electricity distribution sector. The result is that Manipur is, gradually but steadily, moving forward on the road to socioeconomic development.